SOCIO-CULTURAL FEATURES OF ECONOMIC ACTIVITY IN LIFE STRATEGIES OF GLOBALIZED SOCIETY - Gerasymova, Elvira (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. States that the analysis of the mechanism of interaction of global economic processes and material production with the national paradigm of socio-economic knowledge is an urgent problem of social philosophy. The basis of this paradigm is created by the nationalsemantic field of economic development of each nation in the new conditions of a globalized society. The aim of the publication is to identify the socio-cultural features of economic activity in the life strategies of a globalized society. The research Research methodology is determined by the historical-sociological, socio-cultural, and socio-philosophical materials. Cultural-historical, analytical, hermeneutic, and comparative methods were the basic research methods. The dialectical method, in turn, provided a study of processes and phenomena of social reality in terms of systemic development and the relationship of events. Research results. The modern world today is characterized by rapid changes in the life strategies of a globalized society, shaped the requirements to the level of socio-philosophical research of economic activity. At the same time, theoretical and methodological approaches to modern concepts of cognition of economic life are changing reflecting the formation of a kind of intellectual style to the analysis of economic activity in a globalized society. The style accumulates the results of the functioning of the socioeconomic system and a way of reproducing the material support of public life, taking into account its historical, socio-cultural features of existence. Discussion. Separately, we can note the research of the value-semantic context of modern society, humanitarian and scientific strategies of Ukraine's entry into the XXI century by famous Ukrainian philosophers V. Andrushchenko, I. Bychko, V. Horskyi, L. Drotianko, S.Krymskyi, M. Mykhalchenko, M. Popovych, and others. Conclusion. The multivariate demonstration of economic existence stems from the unlimited space of meanings, primarily of socio-cultural principles, and therefore the loss of orientation in meaningful life approaches always leads to the deformation of the traditional system of goals and values of human existence, inherent in the Ukrainian community, increases the probability of demonstration in social relations of systemic errors and utopias. That is why the search for specific forms of organization of economic activity in the broad sense of this category for each national socio-economic system, taking into account the historical, temporal, spatial, and other internal and external factors of the world order is intensifying.